2014
DOI: 10.1021/ic5000205
|View full text |Cite
|
Sign up to set email alerts
|

Photosolvolysis ofcis-[Ru(α-diimine)2(4-aminopyridine)2]2+Complexes: Photophysical, Spectroscopic, and Density Functional Theory Analysis

Abstract: The photochemical and photophysical properties of the cis-[Ru(II)(α-diimine)2(4-APy)2](2+) complexes, where α-diimine = 1,10-phenanthroline (phen) and 4-APy = 4-aminopyridine I, 4,7-diphenyl-1,10-phenanthroline (Ph2phen) II, 2,2'-bipyridine (bpy) III, and 4,4'-dimethyl-2,2'-bipyridine (Me2bpy) IV, are reported. The four complexes were characterized using high-performance liquid chromatography, (1)H NMR, UV-visible, emission, and transient absorption spectroscopy. Upon photolysis in acetonitrile solution these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 119 publications
(347 reference statements)
0
33
0
Order By: Relevance
“…S11†), in agreement with our TEAS characterization and previous experimental and theoretical work performed on analogous systems. 21,25 …”
Section: Resultsmentioning
confidence: 99%
“…S11†), in agreement with our TEAS characterization and previous experimental and theoretical work performed on analogous systems. 21,25 …”
Section: Resultsmentioning
confidence: 99%
“…60,62,63 It is noteworthy that the key actors involved in the mechanism for ligand photorelease from ruthenium complexes have been studied theoretically with monodentate departing ligands only, using a combination of unrestricted DFT and TD-DFT. 29,30,32,33,[67][68][69][70][71] This reaction proceeds along a rather intuitive reaction coordinate, i.e. Ru-L elongation, which can be probed by relaxed surface scans.…”
Section: Introductionmentioning
confidence: 99%
“…Ru-L elongation, which can be probed by relaxed surface scans. 29,30,32,33,69 Mechanistic studies have 6 emphasized the complexity and the multistep nature of ligand photolabilisation processes. 30,67,70,71 However, following an in-depth study of the 3 PES, we have identified new structural isomers of the 3 MC state and have shown that, in addition to bond elongation, the reaction may also involve an offset of the departing ligand from its initial coordination axis.…”
Section: Introductionmentioning
confidence: 99%
“…2+ complexes [50]. The monodentate ligands permit reasonably facile photosolvolysis, which is different from the work emphasized above.…”
Section: Lever and Carlos Led An International Team That Characterizementioning
confidence: 69%